Hormonal modulation of reproduction and fertility signaling in polistine wasps. Issue 5 (15th March 2021) - Oi, Cintia Akemi; da Silva, Rafael Carvalho; Stevens, Ian; Ferreira, Helena Mendes; Nascimento, Fabio Santos; Wenseleers, Tom
Abstract: In social insects, it has been suggested that reproduction and the production of particular fertility-linked cuticular hydrocarbons (CHC) may be under shared juvenile hormone (JH) control, and this could have been key in predisposing such cues to later evolve into full-fledged queen pheromone signals. However, to date, only few studies have experimentally tested this "hormonal pleiotropy" hypothesis. Here, we formally test this hypothesis using data from four species of Polistine wasps, Polistes dominula, Polistes satan, Mischocyttarus metathoracicus, and Mischocyttarus cassununga, and experimental treatments with JH using the JH analogue methoprene and the anti-JH precocene. In line with reproduction being under JH control, our results show that across these four species, precocene significantly decreased ovary development when compared with both the acetone solvent-only control and the methoprene treatment. Consistent with the hormonal pleiotropy hypothesis, these effects on reproduction were further matched by subtle shifts in the CHC profiles, with univariate analyses showing that in P. dominula and P. satan the abundance of particular linear alkanes and mono-methylated alkanes were affected by ovary development and our hormonal treatments. The results indicate that in primitively eusocial wasps, and particularly in Polistes, reproduction and the production of some CHC cues are under joint JH control. We suggest that pleiotropic links between reproduction and the production of such hydrocarbon cues have been key enablers for the origin of true fertility and queen signals in more derived, advanced eusocial insects.